Produk Berstruktur Islam sebagai Instrumen Pelaburan Kompetitif dalam Pasaran Modal Islam di Malaysia: (Islamic Structured Products as a Competitive Investment Instrument in the Islamic Capital Market in Malaysia) - Sulaiman @ Mohamad, Ahmad Azam; Sallehuddin, Siti Syazwani (Online Journal of Research in Islamic Studies, 2024)
Islamic structured products represent an innovative, competitive, and dynamic investment avenue within Malaysia’s Islamic capital market. These products benefit investors by not only offering returns but also protecting their investment capital. This study aims to compare the derivative instruments used and the different investment periods between the Product Highlights Sheet Islamic Dual Currency (PHS IDCI) structured by Maybank Islamic Berhad and the Product Disclosure Sheet Islamic Structured Forward (PDS Islamic Range Forward) by RHB Islamic Bank Berhad. A content analysis method was applied to the documents of both products. The findings indicate that IDCI tends to have a shorter investment period, ranging from one week to two months, whereas the Islamic Range Forward is more flexible, spanning several months to several years. In terms of investment risks, IDCI faces currency risk, option risk, liquidity risk, and market disruption risk, while the Islamic Range Forward encounters credit risk, market risk, and option risk. In conclusion, this study provides a deep understanding of the differences between Islamic structured products at Maybank Islamic Berhad and RHB Islamic Bank Berhad, impacting investment strategies and capital protection for Islamic investors in Malaysia.